White matter integrity in schizophrenia and bipolar disorder: Tract- and voxel-based analyses of diffusion data from the Connectom scanner - Mamah, Daniel; Ji, Andrew; Rutlin, Jerrel; Shimony, Joshua S. (NeuroImage clinical, 2019)
Diffusion imaging abnormalities have been associated with schizophrenia (SZ) and bipolar disorder (BD), indicating impaired structural connectivity. Newer methods permit the automated reconstruction of major white matter tracts from diffusion-weighted MR images in each individual's native space. Using high-definition diffusion data from SZ and BP subjects, we investigated brain white matter integrity using both an automated tract-based and voxel-based methods. Using a protocol matched to the NIH (Young-Adult) Human Connectome Project (and collected on the same customized ‘Connectom’ scanner), diffusion scans were acquired from 87 total participants (aged 18–30), grouped as SZ (n = 24), BD (n = 33) and healthy controls (n = 30). Fractional anisotropy (FA) of eighteen white matter tracks were analyzed using the TRACULA software. Voxel-wise statistical analyses of diffusion data was carried out using the tract-based spatial statistics (TBSS) software. TRACULA group effects and clinical correlations were investigated using analyses of variance and multiple regression. TRACULA analysis identified a trend towards lower tract FA in SZ patients, most significantly in the left anterior thalamic radiation (ATR; p = .04). TBSS results showed significantly lower FA voxels bilaterally within the cerebellum and unilaterally within the left ATR, posterior thalamic radiation, corticospinal tract, and superior longitudinal fasciculus in SZ patients compared to controls (FDR corrected p < .05). FA in BD patients did not significantly differ from controls using either TRACULA or TBSS. Multiple regression showed FA of the ATR as predicting chronic mania (p = .0005) and the cingulum-angular bundle as predicting recent mania (p = .02) in patients. TBSS showed chronic mania correlating with FA voxels within the left ATR and corpus callosum. White matter abnormality in SZ varies in severity across different white matter tract regions. Our results indicate that voxel-based analysis of diffusion data is more sensitive than tract-based analysis in identifying such abnormalities. Absence of white matter abnormality in BD may be related to medication effects and age. •Our study investigated white matter integrity in 87 young schizophrenia, bipolar disorder and control subjects with a tract-based (TRACULA) and a voxel-based (TBSS) approach, using high-definition diffusion imaging data obtained from the Human Connectome Project ‘Connectom’ scanner.•TRACULA evaluated fractional anisotropy (FA) from 18 white matter tracts. TBSS evaluated regional white matter FA.•TRACULA identified a trend towards lower tract FA in schizophrenia subjects across multiple tracts. TBSS results showed mainly unilaterally decreased FA voxels in schizophrenia subjects. FA in bipolar patients did not significantly differ from controls with either method.•With TRACULA, multiple regression showed that anterior thalamic radiation FA predicted chronic affectivity and cingulum-angular bundle FA predicted recent mania in patients. With TBSS, chronic mania correlated with FA voxels within the left anterior thalamic radiation and corpus callosum.